PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 001 TINAMBUNG KABUPATEN POLEWALI MANDAR - Nur Ashilah Luthfiah; Widya Karmila Sari Achmad; Amir Pada (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the implementation of the cooperative learning model of the Take and Give type on the learning outcomes of Natural and Social Sciences (IPAS) of fifth-grade students at SDN 001 Tinambung, Polewali Mandar Regency. This study employed a quantitative approach with a quasi-experimental research design using the Nonequivalent Control Group Design. The research sample consisted of two classes, namely class VA as the control group and class VB as the experimental group, each comprising 18 students. The results of this study indicate that the Take and Give learning model has an effect on students’ IPAS learning outcomes, as seen from the increase in the average scores based on descriptive analysis. Furthermore, inferential analysis showed that the data were normally distributed and homogeneous. Hypothesis testing using the Independent Sample t-test revealed a significant effect on IPAS learning outcomes. It can be concluded that the research conducted in grade V at SDN 001 Tinambung shows that: (1) the implementation of the learning process using the Take and Give learning model in grade V at SDN 001 Tinambung was carried out effectively at each stage and categorized as very good; (2) the IPAS learning outcomes of fifth-grade students at SDN 001 Tinambung, Polewali Mandar Regency, after the application of the Take and Give learning model reached a very good category; and (3) the Take and Give learning model has a significant effect on the IPAS learning outcomes of fifth-grade students at SDN 001 Tinambung, Polewali Mandar Regency.